Assessing the Impact of Technology Learning and Assessment Method on Academic Performance: Review Paper - Tawafak, Ragad M.; Awanis, Romli; Ruzaini, Abdullah Arshah; Almaroof, Rana A. Saeed (MODESTUM, 2018)
Technology enhancement learning is a process that leads to deep point of learning and adds knowledge of technologies. Various studies shed light on technology development and its effect in educational sector. The aim of this integrative review is to examine the current evidence of the impact of technology learning on student learning and academic performance in courses requiring collaborative or activities. The authors searched electronic databases for relevant articles, with different learning techniques. 24 articles met the requirement of paper, it’s collected from (2011-2017). Three themes of techniques used for student learning outcomes, includes technology enhanced learning, assessment method and faculty experience on academic performance in universities with technology use. The final results of this paper show the relationship between what has been done and the factors used by the authors. Also the future work needs more use of technologies in different phases of learning process.